THE EFFECTS OF TART CHERRY SUPPLEMENTATION ON SLEEP QUALITY, EXERCISE RECOVERY AND CARDIOMETABOLIC HEALTH - A LITERATURE REVIEW - Filip Matusiak; Klaudia Brzoza; Michał Kociński; Patryk Iglewski; Michał Pietrasz; Anna Komarczewska (International Journal of Innovative Technologies in Social Science, 2026)
Background: Tart cherry (Prunus cerasus L.) is a rich source of bioactive compounds, such as anthocyanins and melatonin, which have been shown to exert antioxidant, anti-inflammatory, and circadian clock modulation effects. Recently, it has been considered in sports medicine and clinical nutrition as a functional food for regulating sleep, recovery, and metabolic health. Aim: The aim of this review is to comprehensively evaluate and summarize the most current scientific literature regarding to the clinical application of tart cherry supplementation within three major categories: sleep quality, exercise recovery, and cardiometabolic health. Materials and Methods: A literature review was conducted after an analysis of randomized clinical trials (RCTs), systematic reviews, and meta-analyses. Studies were included based on the following criteria: high-quality evidence for studies investigating Prunus cerasus products (juice concentrate, powder) in relation to physiological markers including sleep efficiency, delayed onset muscle soreness (DOMS), blood pressure, and inflammatory biomarkers. Results: The review suggests that tart cherry supplements have a beneficial effect on sleep duration and quality, which may be due to the synergistic combination of melatonin and anti-inflammatory compounds. In sports, chronic supplementation protocols (loading phase) modulate strength decrement and muscle soreness more efficiently compared with an acute dosing strategy. In addition, regular consumption lowers systolic blood pressure (SBP) and enhances cognitive function in the elderly. Conclusions: Tart cherry supplementation is a valid and efficacious evidence-based intervention to improve sleep quality and exercise recovery. However, efficacy is dose-dependent and requires consistent long-term supplementation.